DIFFERENCES IN THE LEVEL OF STRENGTH WITH STUDENTS OF DIFFERENT SPORTS DIRECTIONS - Tijana Krsmanović; Radenka Kovačević; Maja Batez (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
On a specimen of 114 tested boys, aged 15, of which 38 tested boys were footballers, 38 basketball players and 38 students who do not practice a sport, the determination of differences in three motoric tests (standing long jump, standing triple jump and throwing medicine ball) was performed in order to evaluate explosive strength. According to Univariate Analysis of Variance and Multivariate Analysis of Variance it was determined that statistically these three groups of tested boys are significantly different in externalizing explosive strength. By further analysis we can see that statistically the groups are significantly different in the long jump and throwing medicine ball tests, while the differences in the triple jump test are not statistically significant. The usage of Discriminative Analysis gave the same results.